A Multilevel Correction Scheme for the Steklov Eigenvalue Problem. (20th August 2015) - Zhao, Qichao; Yang, Yidu; Bi, Hai
Abstract : Combining the correction technique proposed by Lin and Xie and the shifted inverse iteration, a multilevel correction scheme for the Steklov eigenvalue problem is proposed in this paper. The theoretical analysis and numerical experiments indicate that the scheme proposed in this paper is efficient for both simple and multiple eigenvalues of the Steklov eigenvalue problem.